Facilitators and barriers for working beyond statutory pension age: A prospective cohort study across 26 European countries - Lars Louis Andersen; Joaquín Calatayud; Rodrigo Núñez-Cortés; Ana Polo-López; Rubén López-Bueno (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: The aging population of European countries highlights the need for extended working lives. This study aims to investigate facilitators and barriers for working beyond the statutory pension age (SPA). METHODS: Using data from waves 1, 2, 4-9 of the Survey of Health, Ageing and Retirement in Europe (SHARE) (2004-2022), we followed 9131 workers with a mean age of 56.9 [standard deviation (SD) 3.5] years from 26 European countries until they surpassed the SPA for their respective country, sex and year of participation. Using robust Poisson regression, we modelled the prospective association of work factors, lifestyle, health, and demographics at baseline with working at least one year beyond the SPA. RESULTS: Participants were followed for 9.5 (SD 3.9) years. After surpassing the SPA by at least one year, 18% were still working. Among the work factors, opportunities for skill development [risk ratio (RR) 1.20, 95% confidence interval (CI) 1.07-1.34] and recognition at work (RR 1.13, 95% CI 1.01-1.26) facilitated working beyond SPA, while time pressure (RR 0.89, 95% CI 0.81-0.97) and poor prospects for job advancement (RR 0.76, 95% CI 0.70-0.83) were barriers. For the other factors, smoking was negatively associated with working beyond the SPA, while living in the northern part of Europe, higher level of education, and being divorced or separated were positively associated with working beyond the SPA. CONCLUSION: This prospective cohort study across 26 European countries identified four modifiable work factors that influenced working beyond the SPA. Addressing modifiable barriers and facilitators at the workplace and through public health initiatives could help extend working lives in Europe.